Whatsapp Panic Attitudes and Practices Facing the Application’s Downtime - Aroca Jácome, Rubén; Aguirre Jiménez, Silvia; Ocaña Ocaña, Andrea; León López, Perla (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This study investigates the attitudes and practices of WhatsApp users in response to Facebook's global service outage in October 2020. It is framed within cultural software studies and examines how users experience and relate to social networking platforms. The research also explores the generational dimension in the use of technology and its impact on social relationships.